COMPARATIVE STUDY OF FACTORS AFFECTING TEACHERS PERFORMANCE AT THE SECONDARY LEVEL - Muhammad Waqas Khan; Dr Abdul Ghaffar; Azmat Ali Shah; Murad Khan (International Journal of Contemporary Issues in Social Sciences, 2024)
This research study was a quantitative survey and the aim was to investigate the comparatively factors that affects teacher’s performance at secondary levels in Dir lower. Population of the study was all public/private male and female teachers teaching at Dir lower. Stratified random sampling method was applied to select 300 teachers were selected as a sample of the study include 75 male and 75 female from public sector and 75 male and 75 female from private sector were selected from Tehsil Adanzai. The tool used in this study was self-developed likert scale questionnaire containing 5 indicators and 25 questions. Data was analyzed by mean, standard deviation and t-test. The result showed that some factors which affect teachers performance at secondary level and also show that affecting ratio of private school teachers is more than public and the affecting ratio of female teachers is more than male teachers mean that private school teachers affect more as compared to public sector teachers and female teachers affect more as compared to male teacher. It is necessary for government to make committee that will work on such factors that how to minimize such factors for the purpose of enhancing teaching learning process and for quality education.